Aspergillus fumigatus –Secreted Alkaline Protease 1 Mediates Airways Hyperresponsiveness in Severe Asthma - Redes, Jamie L; Basu, Trisha; Ram-Mohan, Sumati; Ghosh, Chandra C; Chan, Eunice C; Sek, Albert C; Zhao, Ming; Krishnan, Ramaswamy; Rosenberg, Helene F; Druey, Kirk M (ImmunoHorizons, 2019)
The hallmark features of allergic asthma are type 2 (eosinophilic) inflammation and airways hyperresponsiveness (AHR). Although these features often comanifest in mouse lungs in vivo, we demonstrate in this study that the serine protease Alp1 from the ubiquitous mold and allergen, Aspergillus fumigatus, can induce AHR in mice unable to generate eosinophilic inflammation. Strikingly, Alp1 induced AHR in mice devoid of protease-activated receptor 2/F2 trypsin-like receptor 1 (PAR2/F2RL1), a receptor expressed in lung epithelium that is critical for allergic responses to protease-containing allergens. Instead, using precision-cut lung slices and human airway smooth muscle cells, we demonstrate that Alp1 directly increased contractile force. Taken together, these findings suggest that Alp1 induces bronchoconstriction through mechanisms that are largely independent of allergic inflammation and point to a new target for direct intervention of fungal-associated asthma.